2020
DOI: 10.5829/ijee.2020.11.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Providing an Optimal Execution Model for Windows Based on Glazing to Reduce Fossil Fuel Consumption (Case Study: Asman Residential Complex of Tabriz)

Abstract: According to statistics provided by the Iranian Statistics Center,40% of energy consumption is related to the housing sector. Windows as a component of exterior wall, Responsible for 20-30% of all energy infiltration. Therefore, the purpose of this study, is to optimize residential windows in cold and dry climate of Tabriz in order to reduce energy consumption. The research method is based on simulation with two methods "parametric optimization" and "genetic algorithm". The research tool is Design Builder soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Increasing the size of the windows to 35%WWR and 45%WWR have also resulted in the same conditions with a higher increase in heating and cooling loads differences. Results reported by Abdoly Naser et al [31] also showed glazing with low emission coating will decrease, heat loss decreased and annual gas consumption. While reflective coatings on the surface of the glass reduce the receipt of solar energy by 90.86% and therefore this type of glazing is not suitable in cold seasons.…”
Section: Evaluati Ng the Effects Of Solar Shading On Buildi Ng Energy Usagementioning
confidence: 85%
“…Increasing the size of the windows to 35%WWR and 45%WWR have also resulted in the same conditions with a higher increase in heating and cooling loads differences. Results reported by Abdoly Naser et al [31] also showed glazing with low emission coating will decrease, heat loss decreased and annual gas consumption. While reflective coatings on the surface of the glass reduce the receipt of solar energy by 90.86% and therefore this type of glazing is not suitable in cold seasons.…”
Section: Evaluati Ng the Effects Of Solar Shading On Buildi Ng Energy Usagementioning
confidence: 85%
“…There are three very important reasons for the high heat losses from windows: window to wall ratio (WWR); window orientation; and type of window glazing [5]. Due to its low thickness, glazing has the highest heat transfer coefficient among the elements of the building's exterior shell and also the window to wall ratio is one of the most important factors in energy consumption in designing buildings in cold climates [6]. Therefore, the purpose of this study is to present the design criteria and implementation of windows in residential buildings in the cold and dry climate of Tabriz in order to reduce energy consumption.…”
Section: *Correspondingmentioning
confidence: 99%
“…Abdoli Naser et al [12] studied the optimal execution model for windows. For optimization, triple-glazed glazing with low emission coating e = 0.1 is recommended.…”
mentioning
confidence: 99%